Servant leadership and job satisfaction: The mediating role of trust and leader-member exchange - Dami, Zummy Anselmus; Imron, Ali; Burhanuddin, Burhanuddin; Supriyanto, Achmad (Frontiers in Education, 2022)
The study aimed to examine the role of trust mediation and leader-member exchange in the influence of servant leadership on job satisfaction. This study used quantitative methods with a sample of 160 lecturers from 26 Christian higher education in Indonesia. This study used the partial least square (PLS-SEM) approach to verify the proposed hypothesis. The results showed that servant leadership has a significant positive effect on job satisfaction, and trust and LMX mediate the influence of servant leadership on job satisfaction. Finally, trust and LMX are complementary mediation effects of servant leadership on job satisfaction.